PG47 Promoting safe simulation, with simulated patients, in remote access learning. (10th November 2020) - Booth, Jane; Hamilton, Carrie; Thame, Anna
Abstract : Introduction: Due to coronavirus lockdown measures, universities and NHS health trusts have requested that SimComm Academy (SCA) support them in adapting their face-to-face simulation training and examinations to alternative virtual mediums. SCA needed to ensure their simulated patients (SPs) were suitably prepared and able to embrace and support this new learning environment. 1 Methods: Since March 2020, SCA has worked with many organisations championing alternative technologies, including running sessions with SPs over various remote mediums, including telephone, Zoom, Google Meet, and Microsoft Teams. Virtual activities include: 1:1 training, telephone training for Covid-19, remote consultations training, live forum theatre, group training, OSCE and OSPA examinations, pre-filming for live training, and two-day simulation workshops. SPs were carefully selected depending on personal attributes, broadband coverage, IT literacy and access to technology. Sessions were developed through close liaison between SCA and the organisation, with the relationship between the organisation and the SP, managed by SCA. Where possible, SPs were fully briefed in advance and contact details swapped (with permission) between the faculty and SPs, in case of issues arising during the session. Results: The majority of sessions exceeded the organisation, SCA and SP expectations. The technology generally worked well, and when it did not or there were last minute changes, organisations' IT support was critical. The following points have been noted: SPs and participants tired more quickly due to screen fatigue and being static. Confusion occurred when appropriate planning had not occurred or if no pre–briefing was available. If contact details were not exchanged, communication during sessions when issues arose proved problematic. Younger SPs tended to be more technology–literate. Trying to fit sessions into tight time slots caused stress and confusion for all. Output was more productive in group sessions when expert facilitation provided clear direction. Discussion: In a short time period, we have had to act on the results above. We conclude that careful SP selection is critical, including testing of IT equipment and ensuring IT literacy. We quickly learnt that contact details for SPs, faculty and IT support should be circulated, ensuring that permission has been agreed. Underestimating the organisation of these events will lead to failure; detailed forward planning is critical, with clarity and clear role/expectation management, and a pre-brief. Regular breaks are necessary to combat screen fatigue and being static. Generous time allocation for online learning and examinations, is essential. Reference: Health Education England ( 2020) COVID-19 tool kit for safe simulation in healthcare, guidance and principles of best practice in simulation-based education and training. https://www.hee.nhs.uk/sites/default/files/documents/COVID-19%20toolkit%20for%20safe%20simulation.pdf